The unwedding eaudiobook - Condie, Ally (2024)
REESE'S BOOK CLUB PICK "Our June Reese's Book Club pick is the perfect summer listen!!! The Unwedding by Ally Condie opens with a wedding at a gorgeous resort in Big Sur... but everything begins to fall apart when the main character Ellery discovers a dead body the morning of the ceremony." – Reese Witherspoon The White Lotus meets Agatha Christie in this bold novel from a #1 New York Times bestselling author: a recent divorcee's exclusive Big Sur resort vacation unravels when she discovers a dead body on the day of a wedding, in this "clever, witty and fast-paced whodunit." (Harlan Coben) Ellery Wainwright is alone at the edge of the world. She and her husband, Luke, were supposed to spend their twentieth wedding anniversary together at the luxurious Resort at Broken Point in Big Sur, California. Where better to celebrate a marriage, a family, and a life together than at one of the most stunning places on earth? But now she's traveling solo. To add insult to injury, there's a wedding at Broken Point scheduled during her stay. Ellery remembers how it felt to be on the cusp of everything new and wonderful, with a loved and certain future glimmering just ahead. Now, she isn't certain of anything except for her love for her kids and her growing realization that this place, though beautiful, is unsettling. When Ellery discovers the body of the groom floating in the pool in the rain, she realizes that she is not the only one whose future is no longer guaranteed. Before the police can reach Broken Point, a mudslide takes out the road to the resort, leaving the guests trapped. When another guest dies, it's clear something horrible is brewing. Everyone at Broken Point has a secret. And everyone has a shadow. Including Ellery.